2010
DOI: 10.5194/acp-10-2521-2010
|View full text |Cite
|
Sign up to set email alerts
|

Ozone profile retrievals from the Ozone Monitoring Instrument

Abstract: Abstract. Ozone profiles from the surface to about 60 km are retrieved from Ozone Monitoring Instrument (OMI) ultraviolet radiances using the optimal estimation technique. OMI provides daily ozone profiles for the entire sunlit portion of the earth at a horizontal resolution of 13 km×48 km for the nadir position. The retrieved profiles have sufficient accuracy in the troposphere to see ozone perturbations caused by convection, biomass burning and anthropogenic pollution, and to track their spatiotemporal trans… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
393
0
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 278 publications
(408 citation statements)
references
References 58 publications
2
393
0
1
Order By: Relevance
“…An independent OE-based ozone profile algorithm, referred to as SOE here, was developed at the Smithsonian Astrophysical Observatory (SAO) (Liu et al, 2010a). It was shown capable of capturing tropospheric ozone signals in OMI measurements that are perturbed by convection, biomass burning, anthropogenic pollution, and transport of pollution.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…An independent OE-based ozone profile algorithm, referred to as SOE here, was developed at the Smithsonian Astrophysical Observatory (SAO) (Liu et al, 2010a). It was shown capable of capturing tropospheric ozone signals in OMI measurements that are perturbed by convection, biomass burning, anthropogenic pollution, and transport of pollution.…”
Section: Introductionmentioning
confidence: 99%
“…In Liu et al (2010a), the profile of partial ozone columns is retrieved at 24 layers and total ozone column is just the sum of partial ozone columns at all layers. In principle, OEbased profile algorithms should have the potential to provide more accurate total ozone estimates than the two primary total ozone algorithms because of its use of a wider wavelength range (270-330 nm) than that used for total ozone (Bhartia and Wellemeyer, 2002;Veefkind et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Several techniques have been used to retrieve tropospheric ozone columns, such as the tropospheric ozone residual (TOR) method using OMI total ozone and MLS stratospheric ozone column measurements (Ziemke et al, 2006;Schroeberl et al, 2007), the direct retrieval of tropospheric ozone (e.g. Liu et al, 2010;Miles et al, 2014;Tuinder et al, 2013;Safieddine et al, 2013), and limb-nadirmatching observations from SCIAMACHY (Ebojie et al, 2014). Recently, also the multi-spectral retrieval of IASI thermal infrared and GOME-2 ultra-violet measurements has been demonstrated (Cuesta et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…We use a block diagonal matrix with no covariances between the tropospheric and the stratospheric blocks, although, our sensitivity studies (not shown) did not show visible effects in ozone abundances caused by this modification. In addition, we updated the retrieval's vertical pressure grid to P i = 2 −i·1.37/2 · 1000 for i = 0, 18 which follows the principles presented by Liu et al (2010) without changing the number of layers (see Table 3). We also tested how sensitive the retrieval is to the selection of the correlation length.…”
Section: Effect Of Modifications On Averaging Kernels and Errorsmentioning
confidence: 99%
“…As part of this line of instruments the Ozone Monitoring Instrument (OMI; Levelt et al, 2006a, b) on-board Earth Observing System (EOS) Aura (Schoeberl et al, 2006) satellite was launched in 2004. Currently, two algorithms are used to retrieve ozone profiles from the OMI measurements: the operational OMO3PR retrieval developed at KNMI (Kroon et al, 2011) and a scientific algorithm developed at NASA (Liu et al, 2010). Both algorithms are based on the optimal estimation retrieval technique (Rodgers, 2000) but they differ in the implementation.…”
Section: Introductionmentioning
confidence: 99%